Pengelolaan Ekowisata Mangrove Berkelanjutan Sebagai Sarana Edukasi dan Pembelajaran IPA di Bale Mangrove Jerowaru Kabupaten Lombok Timur - Idrus, Agil Al; Gunada, I Wayan; Idawati, Sri; Nirmala, Siska Ayu; Yahdi, Yahdi; Munib, Munib; Dewi, Earlyna Sinthia (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to explore how ecotourism management involving environmental education can increase community awareness and involvement in mangrove conservation. This research design is descriptive qualitative research. The research sample was determined randomly for visitors to Bale Mangrove Ecotourism. The research instrument used questionnaire sheets and interview guidelines with managers, visitors, and the surrounding community as well as observation sheets of ecotourism practices in the area. The research data consisted of responses from structured questionnaires, interviews and qualitative analysis methods, including thematic coding and content analysis, were used to categorize and interpret the responses. The results showed that mangrove ecotourism in Bale Mangrove not only provides economic benefits to the local community, but also acts as an effective educational medium to increase knowledge about the importance of mangrove conservation. With an approach that involves community empowerment and environmental education, it is expected that the management of this ecotourism can provide a sustainable model that benefits both economically and ecologically.